Beirut law school and its place for continued Roman law traditions in late Antiquity and the Middle ages - Novkiriska-Stoyanova, Malina (Law Journal of New Bulgarian University, 2021)
The review is dedicated to a new and analytical legal and historical study of Dr. Piotr Sadowski, professor of Roman law at the University of Opole, Poland for the Beirut Law School, its teachers, students and its significant place as one of the three imperial law schools (along with Rome and Constantinople), approved by the Emperor Justinian, as well as its place for the continuation of Roman tradition in late Antiquity and the Middle Ages.